PENGGUNAAN METODE THINK PAIR AND SHARE DALAM PENINGKATAN PEMBELAJARAN IPS SISWA KELAS V SD - fahriani, ika (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Ika Fahriani Nurhidayati, Joharman, H Setyo BudiPGSD FKIP Universitas Sebelas Maret Surakarta Jl. Kepodang 67A Panjer Kebumene-mail: ikafahrie@gmail.com Abstract: The Using Think Pair and Share Method in Increasing Social Learning of 5th Grade Student Elementary School. The purposes of this study (1) to describe the steps Think Pair Share Method in improving social studies learning V grade students of elementary school. (2) to determine the increase in social studies learning through the use Think Pair and Share Method. (3) to identify the obstacles encountered in the use Think Pair and Share methods and ways to solve. This study was classroom action research conducted in two cycles. Each cycle consists of the planning, execution, observation, and reflection. The subjects were all V grade students. Data collection techniques in this study consists of tests, interviews, and observations. The result conclude that Think Share Pair Method can be increasing social studies learning.Key words: social studies, think pair and share, learning Abstrak: Penggunaan Metode Think Pair and Share dalam Peningkatan Pembelajaran IPS Siswa Kelas V SD. Tujuan penelitian ini adalah (1) untuk mendeskripsikan langkah-langkah penggunaan MetodeThink and Pair Share dalam peningkatan pembelajaran IPS siswa kelas V SD. (2) untuk mengetahui peningkatan pembelajaran IPS melalui penggunaan Metode Think Pair and Share pada siswa kelas V SD. (3) untuk mengidentifikasi kendala yang ditemui pada penggunaan Metode Think Pair and Share dan cara memecahkannya dalam peningkatan pembelajaran IPS siswa kelas V SD. Penelitian ini dilaksanakan dalam dua siklus. Setiap siklus terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah seluruh siswa kelas V SD. Teknik pengumpulan data dalam penelitian ini terdiri dari tes, wawancara, dan observasi. Kata Kunci: think pair and share, pembelajaran, IPS